The Influence of Price and Service Quality on Customer Satisfaction of Indo’ Botting Services Damang Classic (Sharia Economic Analysis) - Herlianti; Usmayani, Ilham Putra (Al-Kharaj: Journal of Islamic Economic and Business, 2024)
This study aims to investigate the impact of price and service quality on customer satisfaction at Damang Classic, seeking to identify the key drivers of customer perceptions and experiences. A quantitative research approach was employed, collecting data from 67 respondents through questionnaires distributed via paper and Google Forms. The analysis utilized multiple linear regression to assess the relationships between the variables. The findings reveal that price does not significantly influence customer satisfaction; however, service quality exhibits a notable positive effect. Additionally, the combined effect of price and service quality is positive and statistically significant, indicating that while price alone is not a determinant of satisfaction, service quality is crucial. These results suggest that businesses like Damang Classic should prioritize enhancing service quality to improve customer satisfaction, as it plays a more critical role than pricing. Understanding this dynamic can help management focus resources effectively. This research contributes to the literature by highlighting the distinct roles of price and service quality in customer satisfaction within the context of Damang Classic, offering insights that can inform strategic decisions in service-oriented industries.